Moldova Financial Sector Assessment Program : Insurance Core Principles--Detailed Assessment Report - World Bank (Washington, DC, 2015)
This assessment reviews the regulatory and supervisory developments in the insurance sector of Moldova. The current assessment is benchmarked against the insurance core principles (ICPs) issued by the International Association of Insurance Supervisors (IAIS) in October 2011 and revised in 2012. The ICPs apply to all insurers, whether private or state-owned. Specific principles apply to the supervision of intermediaries. The assessment covers the supervisory practices of the Comisa Nationala a Pietei Financiare (National Commission for Financial Markets (NCFM)) which began operations in 2007. The recent decision to move from a pure compliance approach to a more risk based methodology needs to be gradual and carefully staged given the technical capacity constraints in Moldova. Insurer risk management is not universally developed so insurers will only be able to effectively move toward a more risk based approach in a series of small and quite specific steps, supported by regulatory clarity. Many shortcomings in the observance of the ICPs will be addressed by a well-structured transition to risk-based supervision (RBS). Group supervision, particularly operational level cooperation and communication with other supervisors, is also an opportunity and a priority. Ensuring the credibility of the regulatory regime will rely on transparent and sustained enforcement.